Interprofessional collaboration in school: Effects on teaching and learning. (November 2019) - Borg, Elin; Drange, Ida
The main objective of this study is to identify and understand interprofessional collaboration practices in schools using a mixed-methods design. First, we conducted a literature review on interprofessional collaboration in schools to give insights into the ways teachers and other professions collaborate with each other, and what kind of interprofessional interventions show positive effects on teaching and learning. Second, we collected data from five Norwegian elementary schools to gain knowledge of factors that facilitate and hinder interprofessional collaboration. The results show that interprofessional collaboration was defined differently in the literature, and that research is lacking on interprofessional collaboration that involves multiple professions in school. Interventions in which social workers and school nurses were involved gave positive, though small-to-moderate, effects on a range of outcome measures. However, interventions that targeted the whole school were found to be the most promising for making changes that persist over time.